Organizaciones Solidarias Creadas por población vulnerable: un estudio de su planificación y gestión interna (2019)
The objective of this paper is to analyze the internal planning and management of solidarity economy organizations established by vulnerable populations. Mixed data collection techniques were used, aimed at associates and managers to evaluate internal processes that influence the productivity and opportunity for social inclusion of the companies studied. The main findings indicate that planning is incipient and the results of internal management are limited by various socio-economic factors, being low level training one of the most significant ones. It is concluded that although the organizations have the support of external professionals in the design and implementation of planning, managers lack the necessary skills to manage the implementation of these processes and economic resources that would allow them to achieve better performance. Keywords: management, solidarity organizations; planning; vulnerable population